2021
DOI: 10.3389/fmolb.2021.717890
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Epithelial-Mesenchymal Transition of Pancreatic Cancer

Abstract: Non-coding RNAs (ncRNAs), or RNA molecules that do not code for proteins, are generally categorized as either small or long ncRNA (lncRNA) and are involved in the pathogenesis of several diseases including many cancers. Identification of a large number of ncRNAs could help to elucidate previously unknown mechanisms in phenotype regulation. Some ncRNAs are encapsulated by extracellular vesicles (EVs) and transferred to recipient cells to regulate cellular processes, including epigenetic and post-transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…More recently, circular RNAs (circRNAs) were shown to proceed differently as they prevent the inhibitory effect of miRNAs on gene expression by binding to their complementary sequences (Meyer et al, 2021). This growing, rapidly evolving field of research and its relationships with EMT in cancer have been recently reviewed (Hussen et al, 2021), and the role of the dysregulated expression of lncRNAs in the pathogenesis of aggressive cancers such as pancreatic ductal adenocarcinoma was particularly emphasized (Takahashi et al, 2021). An important point was the interplay observed between lncRNAs and the biogenesis of CSCs (McCabe and Rasmussen, 2021).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…More recently, circular RNAs (circRNAs) were shown to proceed differently as they prevent the inhibitory effect of miRNAs on gene expression by binding to their complementary sequences (Meyer et al, 2021). This growing, rapidly evolving field of research and its relationships with EMT in cancer have been recently reviewed (Hussen et al, 2021), and the role of the dysregulated expression of lncRNAs in the pathogenesis of aggressive cancers such as pancreatic ductal adenocarcinoma was particularly emphasized (Takahashi et al, 2021). An important point was the interplay observed between lncRNAs and the biogenesis of CSCs (McCabe and Rasmussen, 2021).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Mechanistically, PCGEM1 acts as a molecular sponge of miR-129-5p to upregulate ETS variant 1 (ETV1) expression ( 18 ). Epithelial-mesenchymal transition (EMT), an essential trigger of cell invasion and migration, is closely associated with cancer progression ( 67 , 68 ). Further functional assays in GC cells demonstrated that PCGEM1 promoted invasion and motility of GC cells through regulating SNAI1 ( 28 , 30 ), a transcription factor that modulates the E-cadherin/N-cadherin ratio and induces EMT ( 69 ) ( Figure 3 ).…”
Section: Functions Of Pcgem1 and Underlying Mechanismsmentioning
confidence: 99%
“…Several long non-coding RNAs (lncRNAs) have been shown to be involved in tumor progression in PDAC, and their detection in plasma or serum have been explored as potential biomarkers [79][80][81]. The Hox transcript antisense RNA (HOTAIR) lncRNA and hexokinase-2 (HK2) expression levels are elevated in the serum of patients with PDAC compared to healthy controls [82].…”
Section: Epigenetic Biomarkers In Pdacmentioning
confidence: 99%